The working pressure research of piston pump RN-3.8 - Kravchenko, Sergey; Popov, Stanislav; Gnitko, Sergey (Eastern-European Journal of Enterprise Technologies, 2016)
The research of working pressure of one-piston pump with a combined compensator of pressure pulsations during the operating cycle is carried out. One of the basic gas law in an isothermal process, namely the law of Boyle-Marriott is employed. The law of piston motion which is driven from the crank-connecting rod mechanism (the axis of the crank shaft is made offset downwards relative to the axis of the piston to reduce the magnitude of lateral forces) is used. The piston drive crank rotation angle, the primary pressure in the compensator are taken into account. The research is needed to ensure a stable high-pressure feed of medium (solution) pumped by the pump, with a reduced level of pulsation. The quantitative dependences of the solution volume in the compensator on the piston movement, the solution feed pressure relative to the crank shaft rotation angle, the minimum required amount of total given volume of combined compensator air (it is 0.02m3) are defined. Practical significance of the obtained results of the research is to develop a piston pump design. It provides a stable feed pressure, moderate pulsation level of the solution, which is pumped.